Delineation of management zones in a peach orchard using multivariate and geostatistical analyses - Oldoni, Henrique [UNESP]; Silva Terra, Viviane Santos; Timm, Luis Carlos; Reisser Junior, Carlos; Monteiro, Alex Becker (Elsevier B.V., 2019)
The soil nutritional management in peach orchards in Southern Brazil is still based on conventional and uniform recommendations, without taking into consideration the spatial variability of the physical environment. This might result in over-application of fertilizers in areas with high nutrient levels and under-application in areas with low nutrient levels, which will cause high heterogeneity in the peach production and fruit quality resulting in a low profit of farmers. The objectives of this work were to characterize the spatial variability of soil and tree attributes, in a peach orchard using classical statistics and geostatistical tools as well as to delineate potential management zones based on the soil and tree attributes using the principal component and fuzzy c-means clustering analyses. A 1.8 ha peach orchard, in Morro Redondo, State of Rio Grande do Sul, Brazil, was selected as the study area and a grid of 101 trees was established. Close to each of these trees, soil samples were collected in the 0 - 0.10 m and 0.10 - 0.20 m layers to determine sand, silt and clay fractions, soil bulk density, volumetric water content, pH in water, organic matter, available phosphorus as well as exchangeable potassium, magnesium and calcium contents. During the years of 2010, 2011 and 2012, peach yield, number of fruits per tree, average fruit weight per individual tree, flesh firmness and total soluble solids content per tree were determined. All data sets were submitted to descriptive statistics and the Kolmogorov-Smirnov test as well as to geostatistical analysis. Principal component and fuzzy c-means clustering analyses were used to delineate the management zones based on the optimal number of clusters identified employing the fuzziness performance index and the modified participation entropy. Results showed high spatial variability of yield and quality of peaches. It was found that the optimal number of management zones for the peach orchard was two and most of the soil and tree attributes presented statistical differences in each defined management zone. The defined management zones based on soil and tree attributes open the opportunity to farmers for site-specific management in the peach orchard, aiming at precision agriculture and directing soil sampling design as well.
Keywords: Prunus persica; Soil and tree attributes; Spatial variability